a Substitutive Relationship Between Learning Mathematics With The Addition Method Of Wisdom Ladder With The Vedict Math Addition Method - Endro Tri Susdarwono (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2020)
This study aims to describe the substitutive relationship between learning mathematics, the method of adding wisdom stairs with the Vedict Math addition method. In this study, the method used was experimental. While the approach used is quantitative. The quantitative approach used includes the Spearman level correlation method. The Spearman level correlation method is applied to determine the level of closeness of the relationship between the independent variable and the dependent variable which contains ranking elements or is related to the order of the data. Based on the results of the Spearman level correlation test in the context of this experimental research, it is concluded that the change in the posttest value of the wisdom ladder addition method creates a substitutive relationship with the change in the posttest value of the vedict math method. So it can be stated that the vedict math addition method can be used as a substitutive for the method of adding the wisdom ladder.